2020
DOI: 10.1101/2020.06.14.20130898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19 in Chile. The experience of a Regional reference Center. Preliminary report

Abstract: During the first pandemic wave Covid-19 reached Latin America cities. Aim: To report clinical features and outcomes associated to Covid-19 in a group of patients admitted during the first wave in a regional reference Center in southern Chile designated to severe and critical cases. Methods: Cases were identified by a compatible clinical picture associated to positive RT-PCR or serological testing. A standard protocol was applied. Results: 21 adult patients (20 diagnosed by PCR, one by serology) were admitted b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…Corona virus disease or simply COVID-19 is an infectious disease which was firstly found as an epidemic on December 31, 2019, in Wuhan, China. 1 , 2 This disease quickly spread across the world as the World Health Organization (WHO) on March 11, 2020, declared it as a pandemic. 3 The patients catching this virus manifest a various spectrum of symptoms from a mild fever to acute respiratory failure, also thromboembolic diseases, and dysfunction or failure of several organs.…”
Section: Introductionmentioning
confidence: 99%
“…Corona virus disease or simply COVID-19 is an infectious disease which was firstly found as an epidemic on December 31, 2019, in Wuhan, China. 1 , 2 This disease quickly spread across the world as the World Health Organization (WHO) on March 11, 2020, declared it as a pandemic. 3 The patients catching this virus manifest a various spectrum of symptoms from a mild fever to acute respiratory failure, also thromboembolic diseases, and dysfunction or failure of several organs.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available evidence on COVID-19 characteristics and clinical features has been based on studies of hospitalized patients, with only a few reports based on population wide datasets [10][11][12][13]. Furthermore, there is only a paucity of studies reporting the clinical characteristics and outcomes of patients in Latin America [11,[14][15][16]. The COVID-19 pandemic represents a significant challenge particularly in low to middle-income countries (LMIC) of the region, as interventions such as social distancing are challenging if not virtually impossible to implement in large overcrowded urban areas, and issues such as concurrent dengue outbreaks and limited testing capacity may further impede efforts to stop the spread [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a total of 94 individuals were enrolled, where 50 corresponded to confirmed cases of SARS-CoV-2 infection (24 women and 26 men), and 44 corresponded to sera collected between June and July 2019, thus regarded as free of SARS-CoV-2 antibodies sera (pre-pandemic samples). All 50 confirmed cases corresponded to unvaccinated patients admitted to the Hospital Base de Valdivia (HBV), Valdivia, southern Chile, from April to November 2020, and they were confirmed by a standard RT-qPCR assay using nasopharyngeal swab samples, as previously described [ 28 ]. At the time of sera collection at the HBV, all were symptomatic cases, presenting different degrees of COVID-19 complications, from very mild to severe, which eventually required hospitalization at the HBV.…”
Section: Methodsmentioning
confidence: 99%